1996
DOI: 10.1093/infdis/174.5.1091
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Monoclonal Antibody to Tumor Necrosis Factor on Survival from Childhood Cerebral Malaria

Abstract: Tumor necrosis factor (TNF) is thought to playa key role in the pathogenesis of cerebral malaria. A double-blind, placebo-controlled trial of an anti-TNF monoclonal antibody (B-C7) comprised 610 Gambian children with cerebral malaria, with mortality and residual neurologic sequelae as primary study end points. Sixty (19.9%) of 302 children who received B-C7 died compared with 64 (20.8%) of 308 children who received placebo (adjusted odds ratio [OR], 0.90; 95% confidence interval [CI], 0.57-1.42). Residual neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
118
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(121 citation statements)
references
References 20 publications
(14 reference statements)
3
118
0
Order By: Relevance
“…A later trial in 302 Gambian children with cerebral malaria compared the use of 5mg/kg of a similar monoclonal anti-TNF-␣ antibody with a control group. 7 This study confirmed the anti-pyretic effect but case fatality was not reduced and there was a significantly increased incidence of neurologic sequelae in the antibody-treated children.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…A later trial in 302 Gambian children with cerebral malaria compared the use of 5mg/kg of a similar monoclonal anti-TNF-␣ antibody with a control group. 7 This study confirmed the anti-pyretic effect but case fatality was not reduced and there was a significantly increased incidence of neurologic sequelae in the antibody-treated children.…”
supporting
confidence: 67%
“…The variation in a small study is large and the effect on parasite clearance time needs to be carefully evaluated in a larger study. Whereas temperature in the Gambian children with cerebral malaria gradually decreased during the first 12 hr after treatment, 7 all patients in this study had transient, repeated temperature peaks during the first few days, which may reflect differences in the clinical manifestations of childhood and adult malaria. The three highest doses of the antibody lowered the FCT compared with the control group and a similar anti-pyretic effect was previously demonstrated by a monoclonal antibody against TNF-␣ in cerebral malaria.…”
Section: Discussionmentioning
confidence: 61%
“…To date, no adjuvant treatment has proved effective in severe malaria; all have been ineffective or harmful. [88][89][90] …”
Section: Asiamentioning
confidence: 99%
“…These proinflammatory cytokines are pyrogenic. TNF plays a central role in causing fever (16). Fluctuating fever is the essential clinical feature of symptomatic human malaria.…”
mentioning
confidence: 99%